Can Migrant Labor Actually Reverse the Impact of Japan’s Aging Society? - Rahel Jechire Kalisang; Sylvia Yazid (Jurnal Hubungan Internasional, 2026)
This article examines the role of migration in the society of the receiving country, especially regarding the country’s survival. In this article, we discuss the role of migrant labor in sustaining Japan’s socio-economic situation, which is threatened by labor shortages caused by an aging population. An aging population is a population in which the elderly outnumber the productive age group, accompanied by an extreme decline in birth rates. Recruiting migrants has long been seen as a solution to an aging society. However, this study seeks to critically analyze whether it is indeed an appropriate solution. This article uses qualitative methods, including a case study approach and content analysis, to compile findings and analyses, and employs the concept of replacement migration in the conceptual framework. Our findings suggest that, coupled with an integrated policy framework and an inclusive society, migrant labor should be sufficient to facilitate the labor shortage occurring in Japan’s aging and declining population. However, migrant labor is only a temporary solution, as government integration policy is the most important factor determining how viable migration is as a solution. Keywords: Migrant Labor; Aging Society; Japan; Replacement Migration.